Implementation of Text Mining-Based Linear Programming in Maintenance Scheduling in Power Plant - Gracia Hatikva Supusepa; Glady Inri Rambert; Mayer Ferdinand Wowor (Journal of Comprehensive Science, 2026)
Overweight and obesity are important risk factors for Type 2 Diabetes Mellitus (T2DM). Fasting Blood Glucose (FBG) examination assesses blood glucose levels after an eight-hour fast. Detecting FBG levels in individuals who are overweight or obese, particularly young adults, is essential for preventing metabolic disorders such as T2DM. This study aimed to describe the fasting blood glucose (FBG) profile of female students with overweight and obesity in the 2023 cohort of the Medical Education Study Program. This study employed a descriptive design with a cross-sectional approach. A total of 30 female students who met the inclusion and exclusion criteria were selected using purposive sampling. Most respondents in both groups had normal FBG levels. In the overweight group, 86.7% were in the normal category and 13.3% in the pre-diabetic category, while in the obese group, 80% had normal levels and 20% were pre-diabetic. No respondents were found in the diabetic category. Increased FBG levels were associated with factors such as a family history of diabetes, frequent consumption of sugary foods and fast food, low physical activity, and inadequate sleep duration. Most female students with overweight or obesity had normal FBG levels; however, the proportion of pre-diabetes was higher in the obese group. These findings indicate that early metabolic disturbances may occur in both groups, particularly among individuals with a sedentary lifestyle and a family history of diabetes.